Measuring the Performance of Batam City Government Using the Balanced Scorecard (BSC) Model - PERMATASARI, Rizka Arsyntha; NGALIMAN, Ngaliman; YANTI, Sri (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to measure the performance of the Batam City Government using the Balanced Scorecard (BSC) approach as a comprehensive performance measurement model. The BSC evaluates four main perspectives: financial, customer (public), internal processes, and organizational learning and growth. This study employs a qualitative descriptive approach, which is suitable for gaining an in-depth understanding of complex phenomena, particularly those related to organizational behavior and public administration. The research was conducted in Batam City, Indonesia, during the period from January to May 2025. The findings indicate that the implementation of BSC provides a holistic overview of budget management effectiveness, public service quality, internal process efficiency, and human resource development within the Batam City Government. The study also reveals that integrated performance measurement can enhance accountability, transparency, and the overall quality of governance. Therefore, the application of BSC in the public sector is considered a relevant strategic tool to support planning and more targeted decision-making.